Exchange Interdependence and Interfirm Interaction: Research in a Simulated Channel Setting - Gundlach, Gregory T.; Cadotte, Ernest R. (Journal of Marketing Research, 1994)
The authors employ a simulated market channel to investigate two properties of interdependence—magnitude and relative asymmetry. Increasing magnitudes of joint dependence are associated with more frequent use of noncoercive strategies, less frequent use of coercive strategies, lower residual conflict, and more favorable evaluations of partner performance. These results support the relational exchange paradigm. Findings for relative asymmetry were not anticipated but are informative. First, an increasing power advantage did not result in the predicted greater use of threats and punishments, although demands and normative statements were more prevalent. Second, one side of the dyad decreased its use of rewards and the other increased its use of rewards, promises, and information persuasion. As predicted, an increasing power advantage (lower relative dependence) is associated with less favorable performance evaluations of exchange partners and less residual conflict.